Exploring Reading Preferences in University Students at Universitas Teuku Umar - Endah Anisa Rahma; Giovanni Oktavinanda; Refanja Rahmatillah; Rusma Setiyana (Proceeding of International Conference on Multidisciplinary Research, 2024)
This research study delves into the reading preferences of university students, aiming to uncover the factors that influence their choices in reading materials. The study employs a qualitative approach, combining observation and interviews in collecting data involving 12 students at Universitas Teuku Umar involved as the respondents. The findings reveal the significant impact of individual interests, academic requirements, and technological advancements on reading preferences. First, the connection between individual preferences and reading choices underscores the importance of personalized and self-directed learning. Besides, people are more likely to engage with reading materials that align with their personal passions and interests Second, regarding academic requirement, the impact of academic requirements on reading preferences reflects the influence of formal education on what individuals choose to read. This finding underscores the importance of a well-rounded education that exposes students to a variety of topics and genres. Last, Embracing technological advancements in reading can facilitate continuous learning and access to a wealth of knowledge. By acknowledging these factors, individuals can make informed choices about their reading preferences, thus contributing to their ongoing development. In summary, the finding that the three factors significantly impact reading preferences underscores the dynamic nature of reading choices. These insights provide valuable guidance for educators, content creators, and individuals seeking to expand their reading horizon.